THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK ENVIRONMENT AND INCENTIVES ON MORALE - Amalia, Frisca Fika; Prayekti, Prayekti (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract Work morale is a feeling that is present in someone when carrying out their work so that they do their work feeling happy and can complete their work quickly and responsibly. The aim of this research is to determine the influence of transformational leadership, work environment and incentives on work morale at the Head Office of Waroeng Special Sambal "SS" Yogyakarta. This research uses a quantitative approach by collecting data using a questionnaire.The sampling technique in this research used non- probability sampling or saturated samples with a total research population of 60 employees at the Wroeng Special Sambal "SS" Yogyakarta Head Office. The data analysis technique uses multiple regression analysis.The results of this research show that transformational leadership has a positive and significant effect on work morale, the work environment has a positive and significant effect on work morale, incentives have a positive and significant effect on work morale. So it can be concluded that transformational leadership, work environment and incentives simultaneously influence work morale.